Effect of Unilateral Iatrogenic Testicular Torsion on the Contralateral Testis in Rats: Prepubertal and Postpubertal - Ahmadnia, Hassan; Dolati, Mahmoud; Ghanadi, Ali Reza; Younesi Rostami, Mehdi; Akhavan Rezayat, Ali Reza (Urology Journal, 2019)
Purpose: The present study was conducted to investigate the influence of hemicastration and age at hemicastration on the contralateral testis weight and function/testosterone production. Materials and Methods: 64 Wistar-derived male rats were divided randomly into 4 groups. Group 1 was named immature intervention, group 2 immaturecontrol, group 3 mature intervention, and group 4mature control. In group 1, rats were hemicastrated at 30 days of age (prepubertal). In group 2, sham surgery (midscrotal incision) was performed atthe same age. In group 3, rats were hemicastrated at 70 days of age (postpubertal) and in group 4,sham surgery was done at the same age. Twenty days after the first surgery, contralateral orchiectomy wasperformed in intervention groups and controls underwent random orchiectomy (left or right). Blood sampling for evaluation of serum testosterone was performed just before second surgery. Results:The mean testis weight (1692 ± 26.7 in group 1 versus 1375 ± 39.7 in group 2; P < .001 and 1760 ± 26.6 in group 3 versus 1425 ± 44.9 in Group 4; P < .001) and the mean testicular weight (mg) per 100 g of body weight (735.8 ± 82.3 in group 1 versus 634.8 ± 84.8 in group 2; P = .005 and 652.4 ± 61.4 in group 3 versus 572.6 ± 97.7 in group 4; P = .03) were significantly greater in hemicastrated rats as to their controls. Also, these parameters was greater in prepubertal group than postpubertalhemicastrated rats. There was no appreciable difference in serum testosterone levels across the 4 groups (P = .77). Conclusion: Our research demonstrated that hemicastration results in compensatory hypertrophy of the remaining testis and it decreases as the animals age. Hemicastration does not lead to reduction in serum testosterone levels and the remaining testis can retrieve a normal serum testosterone level.